2009
DOI: 10.1097/pas.0b013e3181b40061
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Immunophenotype of Nephrogenic Adenoma

Abstract: Nephrogenic adenoma (NA) is a rare benign lesion of the urinary tract. Although its histogenesis is still debated, several reports suggest that the lesion has a renal tubular cell origin or differentiation. As NA can be difficult to distinguish from malignant conditions such as prostate cancer, there is a need for reliable markers. Unfortunately, it has been reported that NA cells also stained positive for the prostate cancer marker alpha-methylacyl-coenzyme A racemase (AMACR). Because all the previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…These immunohistochemical results are all in accordance with those previously reported in adult nephrogenic adenomas [13][14][15][16]. A study by Fromont and colleagues reported nonspecific positive staining for P504S and CDIO in nephrogenic adenomas as a result of the use of avidin-biotin detection procedure reacting with the high level of endogenous biotin [14]. The P504S and CDIO antibodies utilized in our study were also detected utilizing an avidin-biotin system and may account for the focal positive reactivity.…”
Section: Discussionsupporting
confidence: 94%
“…These immunohistochemical results are all in accordance with those previously reported in adult nephrogenic adenomas [13][14][15][16]. A study by Fromont and colleagues reported nonspecific positive staining for P504S and CDIO in nephrogenic adenomas as a result of the use of avidin-biotin detection procedure reacting with the high level of endogenous biotin [14]. The P504S and CDIO antibodies utilized in our study were also detected utilizing an avidin-biotin system and may account for the focal positive reactivity.…”
Section: Discussionsupporting
confidence: 94%
“…Most NA express PAX-2 ( Figure 3f) and PAX-8 and AMACR. 11 PSA and PAP are negative. Cytoplasmic 34bE12 staining is found in >50% of cases.…”
Section: Basal Cell Hyperplasia (Bch)mentioning
confidence: 95%
“…Nephrogenic adenoma is a separate disease entity, first described by Davis in 1949 [5] and most commonly comprising small lesions (<1cm) located within the bladder (80%) [6] and histologically resembling distal renal tubules [7]. Whilst nephrogenic adenomas are benign, they can however mimic prostatic adenocarcinoma when located in the prostatic urethra, unless differentiated by immunostaining [6].…”
Section: Introductionmentioning
confidence: 99%